Metabolism of TM‐2, a potential antitumor drug, in rats by using LC–MS. Issue 6 (March 2014) - Men, Lei; Lin, Hongli; Zhao, Yunli; Liu, Hui; Yang, Mingjing; Fan, Ronghua; Wang, Pei; Tang, Xing; Yu, Zhiguo
<x xml:space="preserve">Abstract</x> TM‐2 (13‐(N‐Boc‐3‐i‐butylisoserinoyl‐4, 10‐β‐diacetoxy‐2‐α‐benzoyloxy‐5‐β‐20‐epoxy‐1, 13‐α‐dihydroxy‐9‐oxo‐19‐norcyclopropa[g]tax‐11‐ene) is a novel semisynthetic taxane derivative. Our previous study suggested that TM‐2 is a promising antitumor analogue. In this paper, the metabolism of TM‐2 was investigated in rats following intravenous administration. Two different types of mass spectrometry—hybrid linear trap quadrupole orbitrap (LTQ‐Orbitrap) mass spectrometry and triple‐quadrupole tandem (QQQ) mass spectrometry—were employed to acquire structural information of TM‐2 metabolites. A total of 17 components were identified as the metabolites of TM‐2 in bile, feces, and urine samples. Accurate mass measurement using LC–LTQ‐Orbitrap‐MS was used to determine the accurate mass data and elemental composition of metabolites thereby confirming the proposed structures of the metabolites. The metabolites proposed were mainly oxidates of TM‐2, including methoxy, hydroxyl, dihydroxy, and trihydroxyl analogues. The major metabolic pathway of TM‐2 was the hydroxylation of the taxane ring or the lateral chain. These important metabolic data serve as a useful resource to support further research of TM‐2.